Bone marrow mesenchymal stem cells tune the differentiation of myeloid-derived suppressor cells in bleomycin-induced lung injury - XiaoSan Su; Liu Yang; YanFeng Yin; Jie Huang; Fei Qiao; Yu Fang; Lu Yu; YinYin Wang; KaiHua Zhou; Jun Wang (Stem Cell Research & Therapy, 2018)
Abstract Background Bone marrow mesenchymal stem cells (BMSC) transfer has been attempted as a therapeutic strategy in experimental lung injury and fibrosis. Reduction of neutrophilic infiltration is one of the mechanisms involved in this effect. However, the mechanisms by which BMSC modulate neutrophil remains unknown. Methods and results Exposure of mice to bleomycin (BLM) resulted in significant accumulation of cells that express neutrophilic markers Gr-1HighCD11b+Ly-6GHighF4/80―CD115―CD49d―. These cells lacked immunosuppressive activity and could not be defined as myeloid-derived suppressor cells (MDSC). When BMSC were administrated to BLM-treated mice, they tuned the differentiation of Gr-1HighCD11b+ toward Gr-1LowCD11b+ cells. Gr-1LowCD11b+ cells exhibited unsegmented nuclei and expressed F4/80, Ly-6C, CD49d, and CD115 markers. These cells had potent immunosuppressive activity and thus could be defined as monocytic MDSC. As a result of such immunoregulation, BMSC mediated a decrease of pro-inflammatory products and amelioration of lung injury in BLM-treated mice. Further study using antibody array showed increased expression of macrophage colony-stimulating factor (M-CSF) in BMSC-treated mice. Accumulation of Gr-1LowCD11b+ cells in BMSC-treated mice was abrogated in M-CSF neutralizing mice. The beneficial effect of BMSC was independent of the ability of the cells to engraft in lung and in vitro coculture study of BMSC with Gr-1+CD11b+ cells showed that the induction of Gr-1LowCD11b+ cells by BMSC was independent of cell-cell contact. Conclusions These results document the generation of Gr-1HighCD11b+ cells in BLM-treated mice, and suggest that BMSC tune the differentiation of Gr-1HighCD11b+ toward Gr-1LowCD11b+ cells and therefore inhibit the progression of BLM-induced lung injury.